Marketing Strategy of Batik Tulis Kenongo to Compete During the Covid-19 Pandemic - Astuti, Harum; Isharijadi, Isharijadi; Styaningrum, Farida (Universitas Negeri Semarang, 2022)
This study aims to analyze the marketing strategy of Batik Tulis Kenongo SMEs to compete during the Covid-19 pandemic. This type of study is a descriptive qualitative. The data sources used are primary data sources through direct interviews with five informants, namely the owner of the Batik Tulis Kenongo SMEs, two employees, and two customers. The data analysis technique used is data reduction, data display and concluding drawing. The results show that the marketing strategies that Batik Tulis Kenongo can use to compete during the Covid-19 pandemic are to focus on competitive prices, take advantage of recommendations from old consumers to increase the targeted market share, online marketing to increase customer buying interest, develop knowledge and human resource skills to increase productivity, focus on maintaining competitive selling prices and expanding the market through online marketing. Further research is expected to be able to measure the effectiveness of the use of social media to support digital marketing so that it can be used as consideration for SME actors in determining marketing strategies.